DIAGNOSIS DAN TATALAKSANA FARINGITIS STREPTOCOCCUS GROUP A - De Luh Pratiwi Angganing Lestari; Ni Putu Satya Deva Jayanti; Tri Wisananda Putra; Putu Utari Fridayanthi; I Gede Ketut Deny Patmantha Putra Tjahyadi; Luh Gde Sita Maharani; Putu Nita Cahyawati (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2022)
Pharyngitis is an infection that occurs in the pharynx due to bacterial or viral infection. The bacteria that most often causes pharyngitis is group A Streptococcus. The method used in writing this article is a narrative review. The results of the literature review found information that in diagnosing pharyngitis caused by group A streptococcus bacteria there are several recommendations. Ideally, a rapid antigen detection test (RADT) and/or a throat culture (throat swab) should be performed. The Centor Score is another method that can be used to determine the cause of pharyngitis. This method is an initial assessment to assist doctors in identifying group A Streptococcus as the cause of pharyngitis based on clinical symptoms that occur in patients. The Centor Score is generally intended for assessment in adult patients. Meanwhile, for children, the McIsaac Score can be used. In addition to the scoring system, there is another alternative scoring system that can be used, namely FeverPAIN. Antibiotics should be given if the patient is confirmed to be infected with bacteria. Antibiotics are generally given for 10 days. Penicillin or amoxicillin are recommended as drugs of choice for patients who do not have a history of allergy to these drugs. This choice was based on price, narrow spectrum, and effectiveness. Based on these results, it can be concluded that a definite diagnosis of group A streptococcus infection can be made through a rapid antigen detection test and/or throat culture. Alternative scoring systems that can be used in clinical practice are Centor Score, McIsaac Score, and FeverPAIN. Penicillin or amoxicillin are recommended as drugs of choice for patients without a history of allergies.